Olfactory Dysfunction in Parkinson’s Disease Patients with the LRRK2 G2385R Variant - Cao, Ming (Neurosci Bull, 2016)
Olfactory dysfunction has been reported in Parkinson’s disease (PD) patients carrying the LRRK2 G2019S variant in Caucasians but rarely in those with the LRRK2 G2385R variant. In this study, we performed genotyping for the LRRK2 G2385R variant in PD patients recruited from the Movement Disorder Clinic of Xuanwu Hospital in Beijing and in healthy controls randomly selected from the Beijing Longitudinal Study on Aging cohort. The “five-odor olfactory detection array”, an olfactory threshold test, was used to assess olfactory function. One hundred and eighty-six participants were enrolled, comprising 43 PD patients without (iPD) and 25 with (LRRK2-PD) the LRRK2 G2385R variant, and 118 healthy controls. Our results showed that the threshold of olfactory identification was significantly worse in PD patients than in controls, but not significantly different between the iPD and LRRK2-PD groups. These findings suggested that although olfactory function in LRRK2-PD patients is impaired, it is similar to that in iPD patients.